Creative Climate and Learning Organization: Factors Contributing to Innovation within the Private Sector - Ismail, Meriam (2002)
Studies on innovation have suggested that organizational creative climate tends to play an important role and is a predictor for innovation. However, lately, the presence of a learning culture in organization tends to equally explain a considerable influencing effect on innovation too. This particular study examined the influence of both those variables 011 innovation and to determine which one of the two could be a better predictor for innovation. The results indicated that both learning culture and creative climate have significant contribution of 58.5% to the explanation of the observed variances in the innovation construct. The learning organization culture separately was found to have a significant stronger relationship with innovation (r = .733) than did the creative climate (r = .473) which implied a larger contribution from the learning organization variable towards innovation. Two learning organization dimensions contributed most to the variances in innovation especially the dimensions of 'Embedded Systems' and 'Systems Connection' which have significant high predictive powers on innovation (Beta = .397, p =.000; Beta = .313, p = .000 respectively) occurring within the sampled organizations as compared to the ten creative climate factors and the rest of the five learning organization dimensions. The study also found that both the creative climate and learning organization factors jointly contributed higher with significance (p = .000) at 67.6% to the explanation of the observed variances in innovation for the MNCs (R2 = .676, F = 14.427) than for the local organizations at 60.2% (R2 = .602, F = 7.476). This study involved a sample of eighteen private organizations across vanous core businesses, manufacturing, finance and insurance, consulting, property developing, engineering, telecommunication, and education services, either local organizations or MNCs within the Federal territory of Kuala Lumpur. The size of the respondents is 259. In addition, the findings showed that there were no significant differences in the mean scores (p > .05) among the three organizational job levels namely the top management, middle management and staff, in the members' perceptions on innovation, creative climate and learning culture. The study also found no significant differences in the mean scores (p > .05) among the small, medium, large and very large organizational population sizes in the members' perceptions on innovation, creative climate and learning culture.